Pasivni nedoločniški polstavki, odvisni od glagolov ukazovanja - Kavčič, Jerneja (Keria (Ljubljana), 2005)
The aim of the paper is, firstly, to outline the Naturalness Theory (NT) as it has developed in its latest version at the University of Ljubljana. Secondly, it investigates the use of passive infinitive clauses dependent on the verbs of ordering (a phenomenon more commonly known from the Latin clause type Caesar pontem fieri iussit) and interprets them in terms of the NT.
Keywords: glagol; grščina; latinščina; lingvistika; nedoločniški polstavki; sintaksa; teorija naravnosti